Zambia: ClimBeR Inception Workshop Report - Rose, Sabrina; Valencia, Lina; Kikulwe, Enoch Mutebi; Nkanyani, Shiluva Chauke; Ghosh, Aniruddha; Amarnath, Giriraj (CGIAR System Organization, 2022)
The CGIAR Initiative on Climate Resilience, ClimBeR, aims to transform the climate adaptation capacity of food, land, and water systems in Zambia and five other low- and middle-income countries, ultimately increasing the resilience of smallholder production systems to withstand severe climate change effects like drought, flooding, and high temperatures. The variability in Zambia’s climate means farmers are challenged by droughts, floods, high temperatures, and increased unpredictability. In response, the government is integrating climate change concerns into its agricultural policy agenda. Under its climate-smart agriculture (CSA) framework, Zambia is promoting various adaptation solutions to sustainably increase productivity and enhance resilience. ClimBeR will contribute to the adaptation priorities outlined in Zambia’s Nationally Determined Contribution and Eighth National Development Plan by strengthening early warning systems and increasing access to climate finance, among other activities. The ClimBeR Initiative in collaboration with the Zambia Ministry of Green Economy and Environment (MGEE) and Ministry of Agriculture organized a workshop to bring together stakeholders from the Ministry of National Development Planning, Water Resources Management Authority (WARMA), Zambia Meteorological Department, Disaster Management and Mitigation Unit (DMMU), along with international agencies, development partners, and civil society. The objective of this workshop was to have a deeper understanding on how to co-produce knowledge and innovations that contribute to building systemic resilience against climate variability and extremes in Zambia.